(untitled) (Berlin, 2003)
The book gives a brief description about several markup and document description languages like TIFF, PDF, HTML, and XML, explain the most important techniques such as migration and emulation, and present the OAIS (Open Archival Information System) Reference Model
Keywords: Digital preservation,Library materials,Bảo quản số hoá,Tài liệu thư viện; Conservation and restoration,Bảo quản và lưu trữ